Beyond Barbour or Back to Basics? The Future of Science-and-Religion and the Quest for Unity - Smedes, Taede Anne 1973- (2008)
Abstract. Reflecting on the future of the field of science-and-religion, I focus on three aspects. First, I describe the history of the religion-and-science dialogue and argue that the emergence of the field was largely contingent on social-cultural factors in Western theology, especially in the United States. Next, I focus on the enormous influence of science on Western society and on what I call cultural scientism, which influences discussions in science-and-religion, especially how theological notions are taken up. I illustrate by sketching the way divine action has been studied in science-and-religion. The divine-action debates may seem irrelevant to theologians because the way divine action is dealt with in science-and-religion is theologically problematic. Finally, I analyze the quest for integration and unity of science and religion that underlies much of the contemporary field of science-and-religion and was stimulated particularly by the efforts of Ian Barbour. I argue that his quest echoes the logical positivist vision of unification and has a strong bias toward science as the sole source of rationality, which does not take theology fully seriously.
Keywords: Scientism; Science and religion; Logical Positivism; Divine Action; Ian Barbour